Medios de comunicación para la apropiación del conocimiento en instituciones educativas (2021)
The objective of this research study was to assess how media describes the appropriation of knowledge in educational institutions in the state of Magdalena (Colombia). Ten semi-structured interviews were conducted and analyzed using grounded theory. The results obtained respond to the use of means in learning spaces to generate competencies (use, interaction, and participation) of the human being in meaningful learning sessions. The results show that the communication process depends on the profile and work of the teacher, number of participants, available teaching tools, and structure of the institution. These create barriers and filters that limit learning. Interactive models, with emerging perspectives on knowledge, influence knowledge appropriation. It is concluded that educational media are affected by the teacher-student’s technological culture, which can cause knowledge gaps for proper educational media use.